The free economic zones effectiveness regulation assessment in the Republic of Belarus - Gromova, Victoria S.; Palonik, Irina S. (Journal of the Belarusian State University. Economics, 2021)
The influence of special economic zones activities regulation mechanism on the their territories investment attractiveness and innovation activities by means of various privileges and preferences to them has been considered. The analysis algorithm of the special economic zones investment (business) attractiveness has been worked out allowing to estimate the attractiveness of any their type and to compare them.